Syntactic Analysis of Chinese Imperative Function in “The Captain” Movie - Cintiawinata Jung; Julina; Rudiansyah (Magister of Linguistic, Postgraduated Program, Universitas Warmadewa, 2021)
This article analyzes the function of imperative sentences contained in the